Academic burnout of digital natives and social sustainability: prevalence and risk factors - Sonja Ivančević; Veljko Dmitrović; Marko Ćirović; Nataša Petrović (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu)
As higher education institutions play a key role in setting a foundation for a sustainable workforce, it is their responsibility to create an environment in which students’ well-being will be preserved. In this regard, contemporary universities encounter a significant challenge – the increasing presence of academic burnout syndrome which negatively affects students’ health, career preparedness, and subsequent job performance. While previous burnout studies mostly focused on Millennial students, this study aims to examine burnout prevalence and risk factors among Generation Z, the first true digital natives. Therefore, the study proposes a conceptual model exploring the impact of seven background factors (demographic and situational) on four dimensions of academic burnout, as well as students’ overall burnout. The model is tested on a sample of university students from Serbia, using the Structural Equation Modelling (SEM) analysis. The results indicate that a quarter of the surveyed students experience overall burnout, while over 60% report experiencing some degree of personal burnout. Furthermore, two confirmed hypotheses reveal that Generation Z’s academic burnout is significantly linked to age and whether students study in their hometown. Three partially confirmed hypotheses suggest that certain academic burnout dimensions are also connected to gender, GPA, and tuition payment.